CORRECTION OF MALNUTRITION IN CANCER P ATIENTS WITH ORAL SUPPLEMENTS (SIPING) - V. M. Khomyakov; A. D. Ermoshina (Исследования и практика в медицине, 2015)
Abstract:Malnutrition occurs in 40 to 80 percent of cancer patients. Malnutrition in cancer patients is associated with poorer overall survival, reduced benefit from surgical and medical therapies, increased therapy-related toxicity, poorer quality of life. Early diagnostics of malnutrition and purpose of nutritional therapy is one of important components of supportive care at all steps of anticancer treatment. The modern tools for evaluation of the nutritional status and the principles of nutritional support at cancer patients, including oral nutritional supplements (siping) are presented in the article.